Elucidation of the dimeric interplay of dual MRAP2 proteins in the zebrafish. Issue 9 (8th February 2021) - Wang, Meng; Zhai, Yue; Lu, Liumei; Zhang, Cong; Li, Na; Xue, Song; Cheng, Daofu; Fu, Shaliu; Liu, Qi; Zhang, Chao
Abstract: The melanocortin receptor accessory protein 2 (MRAP2) plays an essential role in the regulation of metabolic homeostasis and deletion of which results in severe obesity syndrome in mice and human. Mammalian MRAP2 is recognized as an endogenous physiological mediator through the potentiation of the MC4R signaling in vivo. Two isoforms of MRAP2 are identified in zebrafish genome, zMRAP2a and zMRAP2b. However, the mechanism of assembling dual topology and the regulatory roles of each complex on the melanocortin cascades remains unclear. In this study, we showed the bidirectional homo‐ and hetero‐dimeric topologies of two zebrafish MRAP2 isoforms on the plasma membrane. Orientation fixed chimeric proteins could affect the trafficking and pharmacological properties of zMC4R signaling. Reciprocal replacement of zMRAP2a and zMRAP2b proteins elucidated the major participation of the carboxyl terminal as the functional domain for modulating zMC4R signaling. Our findings revealed the complex and dynamic conformational regulation of dual zebrafish MRAP2 proteins in vitro. Abstract : 1. The bidirectional homo‐ and hetero‐dimeric topologies of two zebrafish MRAP2 isoforms on the plasma membrane. 2. Orientation fixed chimeric proteins could interact and affect the trafficking and pharmacological properties of zMC4R signaling. 3. Reciprocal replacement of zMRAP2a and zMRAP2b proteins elucidated the major participation of the carboxyl terminal as the functional domain for modulating zMC4R signaling.